(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This bibliometric assessment delves into the evolving relationship between yoga and sports science, exploring the interdisciplinary convergence of ancient holistic practices and modern athletic performance optimization. With a systematic approach employing the Web of Science database, this study analyzes 111 scholarly documents published between 2013 and 2023, providing insights into thematic trends, prolific authors, influential journals, and global contributions. The research showcases a steady annual growth rate of 4.14%, indicating a sustained interest in the subject. Collaborative efforts are evident, with an average of 4.47 co-authors per document and 18.92% international collaborations. The United States emerges as a research leader with 41 articles, closely followed by Australia, Canada, and China. These contributions highlight the multifaceted benefits of yoga in enhancing athletic prowess, injury prevention, and overall well-being. As global interest intensifies, this analysis underscores the importance of interdisciplinary cooperation and cross-cultural exploration to harness yoga’s potential within sports science for informed practices and future advancements.